Hopewell Settlement Patterns, Subsistence, and Symbolic Landscapes - Wymer, DeeAnne; Byers, A. Martin, 1937- (Book collections on Project MUSE., 2010)
This collection of essays addresses important questions, like these and others, by examining the cultural and social nature of the well-known Ohio Hopewell monumental earthworks. Scholars discuss the purpose, meaning, and role of earthworks and other artifacts, theorizing on how they may have reflected political, social, and practical ecological organization.